Protection of Galvanized Steel with Silanes: Its Comparison with Chromium (VI) - Seré, Pablo Ricardo (2014)
The corrosion behavior of hot dip galvanized steel (HDGS) pre-treated with mercaptopropyltrimethoxysilane and a commercial sulfur-bearing silane was studied. Electrochemical polarization, electrochemical impedance spectroscopy, and electrochemical noise tests showed that silane coatings have a corrosion protection performance similar to the usual hexavalent chromium HDGS passivation treatments. It is also evident that the silane films protect the zinc surface through the formation of an isolating barrier. Through voltamperometric studies it was possible to define an electrochemical porosity of the protective coatings. Based on copper sulfate tests and electrochemical porosity results the films protection capability was evaluated, showing that silane treatments have similar or even better protection performance than standard chromium passivation.